An IPtel architecture based on the SIP protocol - Sousa, João Paulo (2012)
More and better accesses to the Internet increase the interest in using it to carry not only data but also voice and video. The IP Telephony (IPTel) was born in this context and offers a framework to create multimedia communication systems. The Session Initiation Protocol, used in the IPTel architecture, is a protocol for signaling and call control between two or more participants. This paper presents telephony over IP service. Different protocols typically used in IPtel are analyzed and the architecture and functionality of SIP protocol are explained. Different mobility modes provided by SIP through the application layer are described. Finally we present the sIPtel, a Java application that supports real audio and video communications and uses the SIP protocol for call signaling.